Close Encounters of the European Kind: Economic Integration, Sectoral Heterogeneity and Structural Reforms - Nauro F. Campos; Vera Z. Eichenauer; Jan-Egbert Sturm (Institute of Labor Economics (IZA), 2020)
This paper addresses two main questions: (a) Has European integration hindered the implementation of labour, financial and product market structural reforms? (b) Do the effects of these reforms vary more across sectors than across countries? Using more granular reform measures, longer time windows and a larger sample of countries than previous studies, we confirm that the euro triggered product but neither labour nor financial market reforms. Differently from previous studies, we find that: (a) the Single Market has similar effects to the euro, and (b) sectoral heterogeneity appears less important in explaining the economic impacts of reforms than country heterogeneity.
Keywords: F4; N1; N4; O4; 330; Euro; Single Market; structural reforms; european integration; sectoral heterogeneity